Streptococcus gordonii infectious endocarditis presenting as a neurocysticercosis mimic — A rare manifestation - Yue Wang; Rui Xu; Maohua Li; Chunmei Duan; Li Wang; Wei Duan (Journal of Infection and Public Health, 2021)
Infective endocarditis (IE) usually presents with nonspecific signs and symptoms, which delay diagnosis and proper treatment. Here, we describe a patient with initial clinical and radiological features compatible with neurocysticercosis who was later found to have IE. Furthermore, the patient course was complicated by multiple neurological complications (brain abscess, meningitis, infected intracranial aneurysm, subarachnoid hemorrhage and hemorrhage), and patient ultimately deceased. To our knowledge, an IE case mimicking neurocysticercosis and progressing with prominent and complicated neurological manifestations has not been previously reported. We therefore describe the challenges of neurocysticercosis diagnosis based on serum ELISA and radiological findings.For patient diagnosed as neurocysticercosis, clinical follow-up is recommended and presence of systemic symptoms should be red flags for another underlying disease.